1951
DOI: 10.1071/ch9510062
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Titanium with Special Reference to the Allotropic Transformation

Abstract: A differential method for determining the thermoelectric power of titanium/platinum thermocouples is described. The results of the differential measurements are compared with data obtained in direct e.m.f. versus temperature determinations. From the thermoelectric power results, the temperature dependency of the following properties has been deduced : (a) the Peltier coefficient of the titanium/platinum couple ; (b) the difference between the Thomson coefficients of titanium and platinum ; (c) the absolute the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1953
1953
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Th e gamma-beta transformation of uranium was found to have been lowered by increasing titanium addi tions, becoming constant at 71 8° C in the vicinity of 5 atomic percent of titaI1ium. The beta-alpha transformation of the alloys appeared consistently at 667° C. Worner [4] showed that r ehea ting of titaniLlpl und er pressure of 10-5 to 5 X 10-5 mm of m er cury elevated andbl'oadened the transformation range of titanium, the influence being attributed to oxygen and nitrogen pickup. It is quite probable that for this reason the purity of titanium used in the alloys for this investigation appeared to have exer ted no appreciable influ ence on the observed temperatures of transformation of uranium, but it was noted th at there were sharper arrests on the cooling curves for alloys con taining titanium produced by the iodide m ethod .…”
Section: Thermal Datamentioning
confidence: 99%
“…Th e gamma-beta transformation of uranium was found to have been lowered by increasing titanium addi tions, becoming constant at 71 8° C in the vicinity of 5 atomic percent of titaI1ium. The beta-alpha transformation of the alloys appeared consistently at 667° C. Worner [4] showed that r ehea ting of titaniLlpl und er pressure of 10-5 to 5 X 10-5 mm of m er cury elevated andbl'oadened the transformation range of titanium, the influence being attributed to oxygen and nitrogen pickup. It is quite probable that for this reason the purity of titanium used in the alloys for this investigation appeared to have exer ted no appreciable influ ence on the observed temperatures of transformation of uranium, but it was noted th at there were sharper arrests on the cooling curves for alloys con taining titanium produced by the iodide m ethod .…”
Section: Thermal Datamentioning
confidence: 99%
“…Data from the most extensive investigation [20] of the properties of these cements are given in Table 111. The values were derived by the methods described in the A.D.A.…”
Section: Dental Cements I 365mentioning
confidence: 99%